SMART SYSTEM FOR DETECTION OF UNDERGROUND CABLE FAULTS USING ARDUINO AND OHM’S LAW - T, Manjula; Nagabhushan; C H, Pushpanjali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Underground cable fault detection plays an important role in power system reliability especially in the urban areas where cables are mostly buried to avoid possible damages due to adverse weather conditions like; heavy rain, snow or thunderstorms Although these subterranean cables are susceptible to failure, pinpointing precisely where the problem occurred to perform the required repairs can be challenging. The proposed system aims to found the range of the exact location of the fault in the underground cable by using the principles of Ohm’s law. Hence, when a low DC voltage is applied at the end of the feeder through a series resistor, the current flow depends on the position of the fault. The components used in this project include an Arduino microcontroller, 16×2 LCD display as a monitor, and switches to sense the open and short circuit faults of the underground cables. It is aimed at providing accurate detection of fault locations so that the necessary repairs can be made without much delay. With these components incorporated, the proposed solution thus provides an effective and economical method of observing the status of underground cables.